2011
DOI: 10.1007/s10340-011-0361-6
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of two systemic neonicotinoid insecticides against pink hibiscus mealybug (Maconellicoccus hirsutus (Green)) on mulberry trees

Abstract: Infestations of the pink hibiscus mealybug, Maconellicoccus hirsutus (Green), in ornamental trees were already in an advanced state at the time of its discovery in the Imperial Valley of California (USA) in August 1999. Initial studies conducted in 2001-2003 provided encouraging results regarding the capacity of both insecticides to severely reduce, and in some cases completely eliminate infestations from individual trees. In 2004-2005, a total of 50 infested mulberry trees (Morus alba L.) were divided into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The highest effect of Imidacloprid and Thiamethoxam had been recorded after 3-4 weeks of treatment. Also, previous results reported that the highest effects of neonicotinoid-based insecticides on mealybugs were recorded after 3 weeks (Willmott, 2012) and 4 weeks of treatment (Castle and Prabhaker, 2011). Despite this, in these studies, the treatments took 3-4 weeks before the highest mortality was observed, which suggest that factors such as water solubility and plant growth rate may affect translocation, thus…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The highest effect of Imidacloprid and Thiamethoxam had been recorded after 3-4 weeks of treatment. Also, previous results reported that the highest effects of neonicotinoid-based insecticides on mealybugs were recorded after 3 weeks (Willmott, 2012) and 4 weeks of treatment (Castle and Prabhaker, 2011). Despite this, in these studies, the treatments took 3-4 weeks before the highest mortality was observed, which suggest that factors such as water solubility and plant growth rate may affect translocation, thus…”
Section: Discussionmentioning
confidence: 78%
“…According to Willmott (2012), Thiamethoxam, a neonicotinoid-based insecticide, provided the highest P. citri mortality. Also, Castle and Prabhaker (2011) reported that there was a significant difference between water control and both Thiamethoxam and Imidacloprid treatments against pink hibiscus mealybug, Maconellicoccus hirstus (Green). Moreover, the same authors reported no significant differences between Thiamethoxam and Imidacloprid.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of a broad selection of insecticides including carbamates [41,42], organophosphates [43,44,45], neonicotinoids [41,42,44,46], pyrethroids [41,42,43], and insect growth regulators [45,47] has been evaluated on pink hibiscus mealybug in the field and laboratory bioassays. However, there is no material registered for pink hibiscus mealybug suppression on dates in California, and the main objective of this study was to identify the best chemical for that purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Some neonicotinoid and pyrethroid insecticides (e.g. imidacloprid, thiamethoxam, bifenthrin) as well as their mixture have provided encouraging results regarding the control of the pest (Castle and Prabhaker, 2011;Fatima et al, 2016). However, the use of some neonicotinoids for outdoor use in EU has been banned.…”
Section: Additional Potential Risk Reduction Optionsmentioning
confidence: 99%